IMPROVEMENT OF FORMING CASH FLOW STATEMENT BASED ON INTERNATIONAL FINANCIAL REPORTING STANDARDS (American Journal of Business Management, Economics and Banking, 2023)
This article describes how to prepare a cash flow statement using the direct method based on International Financial Reporting Standards. In our country, only the direct method is used in the preparation of cash flow statements, so the introduction of the direct method by us will help to increase investor confidence in financial statements.